2016
DOI: 10.1371/journal.pone.0168289
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Chemical Characterisation of Byzantine Glass Weights

Abstract: The understanding of the glass trade in the first millennium CE relies on the characterisation of well-dated compositional groups and the identification of their primary production sites. 275 Byzantine glass weights from the British Museum and the Bibliothèque nationale de France dating to the sixth and seventh century were analysed by LA-ICP-MS. Multivariate statistical and graphical data analysis discriminated between six main primary glass types. Primary glass sources were differentiated based on multi-dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 54 publications
0
66
0
2
Order By: Relevance
“…It should be borne in mind, however, that in some cases the CoO/NiO ratio of the colorant may be distorted for low cobalt concentrations due to overall elevated heavy element levels in certain base glass types. For instance, the nickel content in ancient colourless raw glass may vary from a few ppm in antimony decoloured glasses (3 ppm < NiO < 7 ppm) up to a few tens of ppm in HIMT (NiO ≈ 20 ppm) or Foy-2 high Fe samples (NiO ≈ 35 ppm) [25]. Manganese decoloured glass has nickel contents in the order of 10 to 15 ppm.…”
Section: Roman Cobalt Oresmentioning
confidence: 99%
See 4 more Smart Citations
“…It should be borne in mind, however, that in some cases the CoO/NiO ratio of the colorant may be distorted for low cobalt concentrations due to overall elevated heavy element levels in certain base glass types. For instance, the nickel content in ancient colourless raw glass may vary from a few ppm in antimony decoloured glasses (3 ppm < NiO < 7 ppm) up to a few tens of ppm in HIMT (NiO ≈ 20 ppm) or Foy-2 high Fe samples (NiO ≈ 35 ppm) [25]. Manganese decoloured glass has nickel contents in the order of 10 to 15 ppm.…”
Section: Roman Cobalt Oresmentioning
confidence: 99%
“…Recent analytical data from our laboratory have revealed the existence of cobalt colorants with comparatively low CoO/NiO ratios (3 < CoO/NiO < 10) in glasses dating to the sixth and seventh centuries CE. In a comprehensive analytical study of Byzantine glass weights, the cobalt signature was identified by the direct comparison of the chemical profile of two cobalt blue samples of the same base glass, probably deriving from the same batch, but with minor variations in elements related to the cobalt colorant [25]. Using the same computational model as before, the mixture of the colouring agent used for the cobalt blue Byzantine glass weights can be approximated as the difference between the non-coloured and cobalt coloured samples of the same primary glass production group (Table 4).…”
Section: Characteristics Of Late Antique Cobalt Colorantsmentioning
confidence: 99%
See 3 more Smart Citations